Evaluation of brown sugar flotation for detecting Queensland and Mediterranean fruit fly (Diptera: Tephritidae) infestation in Australian cherries. (January 2022) - Balagawi, Solomon; Broughton, Sonya; Liang, Weiguang; Archer, John; Cruickshank, David; Cruickshank, Christine; Barchia, Idris; Stevens, Mark M.
Abstract: Sugar flotation procedures have been used for many years to separate insects from soil and other substrates. In this study we investigated whether brown sugar flotation (BSF) could be used for detecting eggs and larvae of Bactrocera tryoni (Froggatt) and Ceratitis capitata (Wiedemann) in cherries. Our first study involved both species and combined BSF with either manually or mechanically crushed fruit to quantify the egg and larval detection ability of BSF in conjunction with these sample preparation methods. A second set of experiments (using B. tryoni only) focused on determining the sensitivity of BSF for detecting fruit fly infestation and determining the proportions of different life stages recoverable. This was done by varying oviposition periods to generate fruits with different infestation levels. Our final experiments were used to develop an optimized cherry fruit sampling regime for detecting B. tryoni using BSF. Wet sieving/maceration of the fruit residue and incubation of the macerated fruit sample to allow further insect development were used to determine the number of eggs and larvae in each test sample that were not detected using BSF. Our results show that BSF is more effective when combined with mechanical (rather than manual) fruit crushing. BSF is highly sensitive, detecting at least one B. tryoni second instar from all the samples tested down to a pest density of 1–5 larvae in one fruit within a 35-fruit sample. BSF was less sensitive for egg detection, however when 6 or more eggs were present within a sample of 35 fruits, the probability of detecting at least one egg was ≥85%. Samples of 35 or 42 cherries provided a higher probability of detecting B. tryoni than larger samples when 1–5 eggs or larvae were present in total. BSF is an effective tool for detecting the presence of fruit fly eggs and particularly larvae in cherries and should be considered for incorporation into the current market access protocol for minimizing fruit fly risk in Australian cherry exports. Highlights: Brown sugar flotation procedure is an effective tool for detecting fruit fly in cherry. Mechanical fruit crushing technique exposes more fruit fly for detection than manual crushing. Current cherry market access protocol should incorporate the brown sugar flotation procedure.